ANALISIS PENGALAMAN PENGGUNA APLIKASI E-ABSENSI VERSI PENGEMBANGAN DI KECAMATAN ARMA JAYA, BENGKULU UTARA - fan, Fanro; Rohati Nely; Supriyanti. Y. I; Dacosta L. A; Sari. O. M; Lestari D (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2025)
Employee attendance during working hours is crucial as it ensures the provision of quality services to the community. Employee attendance is regulated by Government Regulation No. 94 of 2021 Article 4 letter f. Starting from January 2, 2023, employees of the North Bengkulu Government are required to use an iOS-based digital attendance system. However, various issues have been encountered, such as difficulties in accessing the attendance website and discrepancies in employee attendance time synchronization. To address these problems, the local government has continued to improve and upgrade the system. The urgency of this research lies in the role of user experience in providing feedback on whether the application fulfills its purpose in achieving effectiveness and efficiency. The research aims to evaluate the user experience of the iOS-based e-attendance application. The study employs an exploratory qualitative method. The research findings indicate that the application is relatively efficient in saving time, energy, and budget. Users expressed satisfaction as the application aligns with their needs. However, internet network instability often causes errors during the e-attendance process. The application is also easy to learn due to its user-friendly design and the consistency of its features, which remained unchanged during the implementation of the 2024 upgrade version of the application policy.